HICP and national CPI in Germany: As similar as possible, as different as needed - Thomas A. Knetsch; Dilyana Popova; Patrick Schwind (Deutsche Bundesbank, 2024)
The Harmonised Index of Consumer Prices (HICP) co-exists with the national Consumer Price Index (CPI) as a key measure of inflation in Germany. Both indices are based on the same granular price data and uniform compilation methods at the lower levels of aggregation. However, differences arise at the upper level, concerning e.g. coverage, index formula, weighting schemes and revision practices. Weighting is a major source of differences but its impact is expected to diminish because, in the last base year changeover, national accounts replaced household budget surveys as the dominant source for deriving five-year fixed CPI weights. This change increases conformity with the annual updating procedure for HICP weights. By contrast, the integration of the cost of owner-occupied housing (OOH) into the HICP might increase the differences between these key measures if, following the ECB's request in its 2020/2021 Monetary Policy Strategy Review, the acquisition approach were implemented. Choosing different options can be rationalized with a number of criteria (e.g. alignment with user interest, main purposes, public acceptance, practicality). As differences matter empirically, communication is important.
Keywords: E31; C43; 330; Inflation measurement; weighting; owner-occupied housing